2000
DOI: 10.1007/s001580050156
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis and optimum design curves for the minimum cost design of singly and doubly reinforced concrete beams

Abstract: This paper reports on the application of the Lagrangian Multiplier Method (LMM) to the minimum cost design of both singly and doubly reinforced concrete rectangular beams under limit state design conditions. Cost objective functions and stress constraints are derived and implemented within the optimisation method. Cost sensitivity analysis, detailed testing and comparisons with conventional design office methods are performed and the results reported, showing that the Lagrangian Multiplier Method can be succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…5 it is observed that the optimum reinforcement in the present model is greater than in the constant stress diagram. The limit for the singly reinforcement is also greater in the present model than in Ceranic et al (2000).…”
Section: Cost In a Singly Reinforced Beam (Srb)mentioning
confidence: 59%
See 3 more Smart Citations
“…5 it is observed that the optimum reinforcement in the present model is greater than in the constant stress diagram. The limit for the singly reinforcement is also greater in the present model than in Ceranic et al (2000).…”
Section: Cost In a Singly Reinforced Beam (Srb)mentioning
confidence: 59%
“…The model is implemented with the costs of the materials, the cost optimization is performed and the results are compared to Ceranic et al (2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the doubly reinforced high-strength concrete T-beams are recommended for structures requiring low height such as parking spaces and bridge decks beams with lower template. The present optimization model is developed for HSC T-beams in exure [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%